Determinations of adipose cell size and number in suspensions of isolated rat and human adipose cells - S W Cushman; L B Salans (Journal of Lipid Research, 1978)
The osmic acid fixation-Coulter electronic counter method described for determining adipose cell size and number in intact adipose tissue fragments has been modified for use with suspensions of isolated rat and human adipose cells. Mean cell sizes in tissue fragments and isolated cell suspensions prepared from the same tissue are virtually identical in rats of various weights. No statistically significant difference in mean adipose cell size between tissue and isolated cell suspension was observed in human adipose tissue although the variability was much greater than in rat tissue. The distribution of cell sizes among replicate samples is more uniform in the isolated cell preparations, possibly reflecting the considerably larger quantities of tissue used in preparing isolated cells than in determining cell size and number directly from tissue fragments. An example of the utility of the modified method during routine metabolic studies with isolated rat epididymal adipose cells is described; isolated cells of increasing size can be obtained from rats of increasing body weight, or from the separated distal and proximal portions of the fat pads of rats of the same weight.